1994
DOI: 10.1111/j.1399-3038.1994.tb00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy and tolerability of topical levocabastine and sodium cromoglycate in the treatment of seasonal allergic rhinoconjunctivitis in children

Abstract: Children (n = 110) with seasonal allergic rhinoconjunctivitis were randomized to receive either twice daily 0.05% levocabastine eye drops and nasal spray plus twice daily topical placebos or 2% sodium cromoglycate eye drops and nasal spray four times daily for a period of 4 weeks. Patients were required to use the nasal sprays as directed and the eye drops only when required. The results obtained suggest that topical levocabastine is at least as effective as sodium cromoglycate for the treatment of this condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Disodium cromoglycate has been one of the common drugs used for allergic rhinoconjunctivitis in children but it is less effective than intranasal glucocorticosteroids or H 1 -antihistamines (2233,2235,2236). It is important to note that in children, these drugs are free from side effects.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Disodium cromoglycate has been one of the common drugs used for allergic rhinoconjunctivitis in children but it is less effective than intranasal glucocorticosteroids or H 1 -antihistamines (2233,2235,2236). It is important to note that in children, these drugs are free from side effects.…”
Section: Treatmentmentioning
confidence: 99%
“…However, although there is a beneficial effect upon symptoms in the organ to which they are administered, they usually have little effect elsewhere. These drugs are useful in children with symptoms limited to the nose or the eyes (1408,2233,2234).…”
Section: Treatmentmentioning
confidence: 99%
“…The present findings may be compared to those of 4 previously published trials [14][15][16][17] in children and adolescents with SAC and seasonal allergic rhinoconjunctivitis. Two of these trials 14,15 showed patient global ratings for levocabastine 0.05% eye drops BID to be higher than those for cromoglycate sodium 2% eye drops QID (P < 0.05).…”
Section: Discussionmentioning
confidence: 81%
“…Two of these trials 14,15 showed patient global ratings for levocabastine 0.05% eye drops BID to be higher than those for cromoglycate sodium 2% eye drops QID (P < 0.05). The third trial 16 compared nedocromil sodium 2% eye drops (BID) with vehicle (control).…”
Section: Discussionmentioning
confidence: 99%
“…Topical mast cell stabilizers, such as cromolyn sodium or nedocromil, have also been found safe in children 48 but not as effective as H 1 -antihistamines or INSs in the treatment of seasonal allergic rhinitis (SAR) 48,[50][51][52] . Mast cell stabilizers provide maximum efficacy when begun prior to symptom onset 33,53 , although relief may take several weeks 54 and frequent dosing (up to six times daily) may reduce compliance 33,48,53 .…”
Section: Drug Classesmentioning
confidence: 99%